The Woodpecker Enterprise / Addina Syaza Abdul Aziz … [et al.] - Abdul Aziz, Addina Syaza; Azmir, Fariesha Syazwani; Mohd Zaki, Muhammad Hafiz; Shaharin, Nur Annisa; Mohd Zurimi, Salmiza Ainatasya (2022)
Since planning a business may have been seen as a piece of cake, it certainly is not an easy route. Planning requires patience along with the readiness of certain entities, preparing themselves before entering the entrepreneur’s hectic world. our company – The Woodpecker, has done the research and planned our business plan thoroughly. It is to make sure to be fully prepared so that we can overcome any hurdles that come our way. This business plan of The Woodpecker has been detailed in terms of the marketing and operation strategies, financial budgets as well as administrative expenses. Therefore, we had narrowed down our targeted public schools which are located in Sarawak, Malaysia. The Woodpecker manufactured school desks set (desk and chair) and sells them at a cheaper price to the government. In a nutshell, The Woodpecker is a social company that helps provide school desks sets that are designed especially for students to give extra comfort throughout the classes. The manufactured school desks sets will be made out of recycled waste. The Woodpecker kills two birds with one stone as we are not only aiming to help public schools that lack facilities but also preserve the environment